2011
DOI: 10.4049/jimmunol.1002127
|View full text |Cite
|
Sign up to set email alerts
|

MEKK3 Regulates IFN-γ Production in T Cells through the Rac1/2-Dependent MAPK Cascades

Abstract: MEKK3 is a conserved Ser/Thr protein kinase belonging to the MAPK kinase kinase (MAP3K) family. MEKK3 is constitutively expressed in T cells, but its function in T cell immunity has not been fully elucidated. Using Mekk3 T cell conditional knockout (T-cKO) mice, we show that MEKK3 is required for T cell immunity in vivo. Mekk3 T-cKO mice had reduced T cell response to bacterial infection and were defective in clearing bacterial infections. The Ag-induced cytokine production, especially IFN-γ production, was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…MEKK3 has been 29 A study also showed that MEKK3 regulates T-cell receptor-mediated ERK1/2, p38, and JNK MAPK activation in CD4 T cells. 15 In our study, we found that MEKK3 is responsible for activation of ERK1/2 and JNK2, but not p38, ERK5, or JNK1, in platelets. Adam et al claimed that JNK1 plays important roles in platelet activation and proposed that JNK2 also contributes to platelet aggregation, based on the observation of further inhibitory effects of the JNK inhibitor SP600125 on the aggregation of JNK1-deficient platelets.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…MEKK3 has been 29 A study also showed that MEKK3 regulates T-cell receptor-mediated ERK1/2, p38, and JNK MAPK activation in CD4 T cells. 15 In our study, we found that MEKK3 is responsible for activation of ERK1/2 and JNK2, but not p38, ERK5, or JNK1, in platelets. Adam et al claimed that JNK1 plays important roles in platelet activation and proposed that JNK2 also contributes to platelet aggregation, based on the observation of further inhibitory effects of the JNK inhibitor SP600125 on the aggregation of JNK1-deficient platelets.…”
Section: Discussionmentioning
confidence: 72%
“…[26][27][28] MEKK3 was reported to activate MAPKs. [14][15][16][17]29 The activation of p38, ERK1/2, JNK1/2, and ERK5 in MEKK3 f/f and MEKK3 2/2 platelets was determined. MEKK3 deficiency did not affect the activation of p38, JNK1, or ERK5, but it greatly impaired the activation of ERK1/2 and JNK2 induced by thrombin, ADP, U46619, or collagen (Figure 4C-D; supplemental Figure 4A-C).…”
Section: Mekk3 Deficiency Impaired the Activation Of Erk1/2 And Jnk2mentioning
confidence: 99%
See 1 more Smart Citation
“…Although molecular details of IKK␣ activation are still cloudy it is noteworthy that MEKK3 is supposed to be located upstream of IKKs (54). A recent report in fact documents the pivotal role of MEKK3 for TCR-driven T cell activation and subsequent engagement of ERK1/2 as well as cytokine production (55). The remarkable potency of the MEK1/2 inhibitor U0126 detected herein to inhibit IL-22 expression is certainly of note in this context.…”
Section: Discussionmentioning
confidence: 95%
“…It seems that NRF2 induction through RAC1 is KEAP1-independent in our model even though KEAP1 overexpression inhibits RAC1 on the formation of E-cadherin-mediated cell-cell adhesion (37). It has been widely reported that RAC1 participates in several signaling kinase pathways, including MAPKs and PI3K (38,39). Our group has reported a KEAP-independent regulation of NRF2 that relies on signaling kinases PI3K/AKT (40).…”
Section: Discussionmentioning
confidence: 97%